Generation of patient-specific induced pluripotent stem cells from Leber's hereditary optic neuropathy - Huai-En Lu (Stem Cell Research, 2018)
Leber's hereditary optic neuropathy (LHON) is a maternally inherited mitochondrial disease caused by homoplasmic point mutations in complex I subunit genes of mitochondrial DNA. In this report, we generated an induced pluripotent stem cell (iPSCs) line, TVGH-iPSC-010-09, from the peripheral blood mononuclear cells of a female patient with Leber's hereditary optic neuropathy (LHON) by using the Sendai-virus delivery system. The resulting iPSCs retained the disease-causing mitochondrial DNA mutation, expressed pluripotent markers and could differentiate into the three germ layers. We believe LHON patient-specific iPSCs provide a powerful in vitro model for evaluating the pathological phenotypes of the disease.